PEMANFAATAN ABU ECENG GONDOK SEBAGAI BAHAN TAMBAH UNTUK MENINGKATKAN KUAT TEKAN BETON (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
Hyacinth plant in Latin terms called Eichhornia crassipes is an aquatic plant that until now is still considered a pest of the gadfly and is very difficult to destroy. This is because hyacinths have very fast growth properties and have good survival. Hyacinth is an aquatic plant that absorbs a lot of water, causing a lot of surface water to decrease a lot to reach four times when compared to an open water surface and this plant can also cause siltation in rivers or swamps, closures in river grooves or other swamp areas. But on the other hand, it shows that hyacinth plants can be used for home industry and also a very high fiber content. If hyacinth is burned, it will produce ash containing silica (SiO2) which can be used to add material to the concrete mixture. This study aims to find out the best variation in the addition of hyacinth ash so as to produce the most optimal compressive strength by adding hyacinth ash starting from 6%, 7.5%, 9%, 10.5%, 12%, 13.5% and 15% to the weight of cement in karaktristic concrete Fc'= 22 Mpa and the concrete compressive strength test is carried out at the age of 28 days. From the test results, it can be seen that the compressive strength of concrete at the age of 28 days obtained the most optimal conditions occurred in the addition of hyacinth ash of 10.5% in concrete mixtures with the resulting cartrictic compressive strength of 25.46 Mpa, this condition led to an increase in the compressive strength of concrete as large as 13.86% of normal concrete.